Effect of electrophoresis time deposition of colloidal gold nanoparticles on inducing the crystallization of amorphous Si thin films. (1st August 2019) - Ghribi, Khaoula; Ouertani, Rachid; Ben Mabrouk, Kaouther; Khirouni, Kamel; Dimassi, Wissem
Abstract: This work investigates the metal induced crystallization of hydrogenated amorphous Silicon (a-Si:H) thin films, processed by plasma enhanced chemical vapor deposition, using Au nanoparticles (AuNPs) as crystallizing mediator metal. Electrophoresis deposition (EPD) of colloidal AuNPs was used to coat the Si substrates before the a-Si:H processing. Then, the crystallization was conducted by isothermal annealing for temperatures above the eutectic (500 and 600 °C). Raman spectroscopy analysis showed that the crystalline volume fraction doubled as the EPD time increases. Scanning electronic microscopy and energy-dispersive X-ray microanalysis revealed that AuNPs induced crystallization at 600 °C was achieved through eutectic reaction with mixing layers. Structural characterizations showed that the low amounts of AuNPs exhibited a metal mediating effect more pronounced than that of continuous Au thin film deposited by dry physical methods. The enhancing effect of AuNPs was assigned to their size dependent high surface energy. Herein, we discuss as well, the effect of the EPD time on the development of Si crystallites on the basis of thermodynamic and kinetic considerations.